Thermal Stability and Luminescent Properties of Tri-cellulose Acetate Composites Containing Dy(SSA)3Phen Complex - Xiangwei Sun; Feiyue Wu; Yan Luo; Mengjun Huang; Yuntao Li; Xiang Liu; Kunpeng Liu (Journal of Chemistry)
Dysprosium (Dy) ternary complex was prepared using 5-sulfosalicylic acid (SSA) as the first ligand and 1,10-phenanthroline (Phen) as the second ligand, denoted as Dy(SSA)3Phen. The complex was blended with tri-cellulose acetate (TCA) via a cosolvent method to obtain polymer luminescent materials. The composition and structure of the rare-earth complex were characterized by means of elemental analysis, infrared (IR) spectra, and thermogravimetric analysis (TGA). The fluorescence spectra displayed this pure Dy(SSA)3Phen complex, and the TCA/Dy(SSA)3Phen composites all emit blue light. The (90/10) composite possesses fine luminescent properties with quantum yield of 33.5% and thermal stability for potential usage as blue fluorescent materials.